O controle de convencionalidade pelo delegado de polícia - Silva, Giuliano Sorge de Paula (2024)
This dissertation aims to demonstrate how the police chief, during the stage assigned to him in criminal prosecution, became an agent of State repression into a legitimate police authority for the protection of rights and guarantees in criminal investigation. The milestone of this transformation is the Federal Constitution promulgated on October 5, 1988, that re-established the democratic rule of law in Brazil and, with that, established rights and guarantees that must be mandatorily observed by public bodies and powers during judicial police acts. This mission occurs through the compatibility of domestic legal instruments with the international human rights treaties and conventions in force before our legal system. Through the control of conventionality in the performance of his duties – essentially in the course of the police investigation –, in the indictment and arrest in flagrante delicto, as well as in the indictment of the investigated, the police chief proceeds to the preliminary adaptation of the domestic norm to the precepts enshrined in international law, making it possible for this important phase of the criminal procedural system of the homeland to be in line with the universally recognized principles, under the rule of the dignity of the human person. In this context, the police chief represents the actions of the State in the search for the effectiveness of human rights